Los estudios irlandeses por todo el mundo 2021 - Maureen O’Connor (Estudios Irlandeses, 2022)
We had such high hopes for 2021. There was a time in the summer when those hopes seemed about to be fulfilled, but for much of the year we were back to where we were the year before. Because of the unrelenting pandemic, some 2021 cultural and academic events relevant to Irish Studies remained virtual, some were held using a blended format, and some events took place in person. Most of the major Irish Studies conferences remained online, such as the British Association for Irish Studies (BAIS), which, ever-innovative, held another month-long conference in May, this time on the subject of the Irish diaspora. This event followed the association’s research day, held on 17 March, which functioned as a wonderful kind of clearing house, a place to learn about all sorts of Irish Studies projects around the world. The event’s Twitter hashtag, #BAISDay2021, continues to be a valuable resource.